An In Vitro Model to Evaluate the Impact of the Soluble Factors from the Colonic Mucosa of Collagenous Colitis Patients on T Cells: Enhanced Production of IL-17A and IL-10 from Peripheral CD4+ T Cells - Kumawat, Ashok Kumar; Nyhlin, Nils; Wickbom, Anna; Tysk, Curt; Bohr, Johan; Hultgren, Olof; Hultgren Hörnquist, Elisabeth (Mediators of Inflammation, 2014)
Soluble factors from intestinal mucosal cells contribute to immune homeostasis in the gut. We have established an in vitro model to investigate the regulatory role of soluble factors from inflamed intestinal mucosa of collagenous colitis (CC) patients in the differentiation of T cells. Peripheral blood CD4+ T cells from healthy donors were polyclonally activated in the presence of conditioned medium (CM) generated from denuded biopsies (DNB) or isolated lamina propria mononuclear cells (LPMCs) from mucosal biopsies from CC patients compared to noninflamed controls, to determine proliferation and secretion of cytokines involved in T-cell differentiation. Compared to controls, we observed significantly increased production of the proinflammatory cytokines IFN-γ, IL-17A, IL-6, and IL-1β and the anti-inflammatory cytokines IL-4 and IL-10 in the presence of CC-DNB-CM. The most pronounced effect of CC-LPMC-CM on peripheral CD4+ T cells was a trend towards increased production of IL-17A and IL-10. A trend towards reduced inhibition of T-cell proliferation was noted in the presence of CC-DNB-CM. In conclusion, our in vitro model reveals implications of soluble factors from CC colonic mucosa on peripheral T cells, enhancing their production of both pro- and anti-inflammatory cytokines.